Tumor growth accelerated by chemotherapy-induced senescent cells is suppressed by treatment with IL-12 producing cellular vaccines - Šímová, Jana; Sapega, Olena; Imrichová, Terezie; Stepanek, Ivan; Kyjacova, Lenka; Mikyskova, Romana; Indrová, Marie; Bieblová, Jana; Bubeník, Jan; Bártek, Jiří; Hodný, Zdeněk; Reiniš, Milan (Oncotarget, 2016)
Standard-of-care chemo- or radio-therapy can induce, besides tumor cell death, also tumor cell senescence. While senescence is considered to be a principal barrier against tumorigenesis, senescent cells can survive in the organism for protracted periods of time and they can promote tumor development. Based on this emerging concept, we hypothesized that elimination of such potentially cancer-promoting senescent cells could offer a therapeutic benefit. To assess this possibility, here we first show that tumor growth of proliferating mouse TC-1 HPV-16-associated cancer cells in syngeneic mice becomes accelerated by co-administration of TC-1 or TRAMP-C2 prostate cancer cells made senescent by pre-treatment with the anti-cancer drug docetaxel, or lethally irradiated. Phenotypic analyses of tumor-explanted cells indicated that the observed acceleration of tumor growth was attributable to a protumorigenic environment created by the co-injected senescent and proliferating cancer cells rather than to escape of the docetaxel-treated cells from senescence. Notably, accelerated tumor growth was effectively inhibited by cell immunotherapy using irradiated TC-1 cells engineered to produce interleukin IL-12. Collectively, our data document that immunotherapy, such as the IL-12 treatment, can provide an effective strategy for elimination of the detrimental effects caused by bystander senescent tumor cells in vivo.
Keywords: kombinovaná terapie; Tumor Burden; bystander efekt; stárnutí buněk; Neoplasms, Experimental; cytokiny; Antineoplastic Agents; interleukin-12; zvířata; myši inbrední C57BL; časové faktory; Immunotherapy, Adoptive; tumor burden; experimentální nádory; Bystander Effect; Male; Interleukin-12; Mice, Inbred C57BL; Cytokines; Taxoids; taxoidy; nádorové buněčné linie; protinádorové látky; Cellular Senescence; Animals; Cell Line, Tumor; Combined Modality Therapy; imunoterapie adoptivní; mužské pohlaví; Time Factors